IS CASSATION RECOURSE AN EFFECTIVE REMEDY IN ADMINISTRATIVE CONTENTIOUS? IS THERE A NEED FOR A REFORM OF THE REMEDIES AND TO REPLACE CASSATION RECOURSE WITH APPEAL? - Cozgarea, Bogdan Ionuț; Cătană, Emilia Lucia (International Journal of Legal and Social Order, 2024)
This study aims to approach the system of remedies in administrative contentious, from legislative, doctrinal and jurisprudential perspectives. From a historical perspective, was recourse the traditional remedy in administrative contentious or not? Under the current legislation, the cassation recourse, an extraordinary remedy, remedy of legality and with a restrictive regime of evidence, is an effective remedy in administrative contentious? Is there a need for a reform in the system of remedies and the replacement of the recourse by appeal? The conclusions of the study present the advantages and disadvantages of each remedy for the purpose of launching a debate on the choice between tradition and modernity.